Building services handbook - Hall, F. (Fred); Greeno, Roger (London : Routledge, Taylor & Francis Group, 2013)
'This seventh edition of Hall and Greeno's leading textbook has been reviewed and updated in relation to the latest building and water regulations, new technology, and new legislation, and even more design calculations have been added. In addition, topics such as: alternative sources of natural energy, solar, ground source, heat pumps, renewable energy sources, geothermal methods, and wind power, are now covered. Building Services Handbook summarises the application of all common elements of building services practice, technique and procedure, to provide an essential information resource for students as well as practitioners working in building services, building management and the facilities administration and maintenance sectors of the construction industry. Information is presented in the highly illustrated and accessible style of the best-selling companion title Building Construction Handbook. THE comprehensive reference for all construction and building services students, Building Services Handbook is ideal for a wide range of courses including NVQ and BTEC National through Higher National Certificate and Diploma to Foundation and three-year Degree level. The clear illustrations and complementary references to industry Standards combine essential guidance with a resource base for further reading and development of specific topics'--
Includes index.
Includes bibliographical references and index.
Keywords: Buildings -- Mechanical equipment -- Installation -- Handbooks, manuals, etc; Building management -- Handbooks, manuals, etc